Awareness Level of College Students on Consumer Protection Practices in Chitwan - Chhetri, Ashmita Dahal (Journal of Balkumari College, 2020)
Any individual who purchases products or services for his personal use is called a consumer. A consumer is one who is the decision maker whether to buy or not to buy an item. And It is true that the consumer is the king of the market, but in reality consumers are treated very badly in the market. The consumers are cheated in different ways by middlemen like adulteration, under-weight of goods, selling goods of inferior quality and duplicated goods, charging higher prices, misleading advertisement in the media, etc. The consumers are not sure of getting qualitative goods as per their demand and price payments. The most important step in consumer education is making them aware about consumer rights and to empower them for self-protection from the different unethical behaviors of the market. Consumer education is an important part of this process. Consumer education at the college level is an important process to enhance the capacity of the youth particularly the students to take the responsibility for their own life, their family, obligations to society and the environment. Consumer education helps the students to participate in the social life, as competent citizens. Students are not only learning about the consumer rights and duties but also teach their parents and the community, thereby they are enriching the society. This research is based on analytical and descriptive research. The method of data collection is based on primary method. The researcher personally involved in the data collection process with the help of structured questionnaire. The method of sampling technique adopted is Convenience sampling. In general, the level of awareness of college students on consumerism is satisfactory. It is found that the practices and behavior during buying process is appreciable.